Análisis de la susceptibilidad a deslizamientos y elementos expuestos de la quebrada Negroyacu en el sector Alpachaca hasta el barrio la Primavera de la ciudad de Guaranda en el periodo agosto - diciembre 2024 - Cadena Talahua, Mariela Melisa (2025)
The current research study focuses on the analysis of the susceptibility to landslides in the Negroyacu ravine, located in the Alpachaca sector up to the La Primavera neighborhood of the city of Guaranda. The main objective of the study is to identify the areas with the greatest susceptibility to landslides and evaluate the elements exposed to this risk, in order to propose preventive and corrective measures, in this project, the analytical research methodology was used, which seeks to understand the causes, explanations and relationships between phenomena, situations of slope instability factors that influence landslides. Additionally, it is descriptive since it explains and analyzes the characteristics, priorities and phenomena that are related to risk management, for the analysis of the slopes in the Negroyacu ravine, the GEO 5 software was used with the Bishop method. For this, data such as the type of soil, its friction and cohesion angle, in addition to a safety factor of 1.50 and a horizontal seismic coefficient of 0.024 gals were introduced, the results obtained allowed to identify the areas with the greatest susceptibility to landslides. In addition, exposed elements such as housing, road infrastructure and service networks were identified. In conclusion, it was established that the Negroyacu ravine has a high degree of susceptibility to landslides. The results obtained allow prioritizing the areas where the competent authorities must intervene.